Passionate work : endurance after the good life - Hong, Renyi, 1984- (Duke University Press, 2022)
"In Passionate Work, Renyi Hong theorizes the notion of being 'passionate about your work' as an affective project that encourages people to endure economically trying situations like unemployment, job change, repetitive and menial labor, and freelancing. Not simply a subject of aspiration, passion has been deployed as means to build resilience and mend disappointments with our experiences of work. Tracking the rise of passion in nineteenth-century management to trends like gamification, coworking, and unemployment insurance, Hong demonstrates how passion can emerge in instances that would not typically be understood as passionate. Gamification numbs crippling boredom by keeping call center workers in an unthinking, suspensive state, pursuing even the most banal tasks in hope of career advancement. Coworking spaces marketed toward freelancers combat loneliness and disconnection at the precise moment when middle-class sureties are profoundly threatened. Ultimately, Hong argues, the ideal of passionate work sustains a condition of cruel optimism, where passion is offered as the solution for the injustices of contemporary capitalism"--